Identification of Potential Clove (Syzygium Aromaticum) Areas and Their Distribution in the Petuanan Negeri Salamahu, Tehoru District, Central Maluku Regency - Wakim, Mesak; Salakory, Melanus (GEOFORUM, 2022)
Clove plants (Syzygium aromaticum) are tropical plants highly suitable for cultivation in Indonesia. They thrive in hot climates with 8 hours of sunlight per day and evenly distributed rainfall. They can be planted and continue to produce at altitudes ranging from 0 to 900 meters above sea level. Additionally, the types of soil suitable for clove cultivation include Andosol, Latosol, Regosol, and Red Podzolic soils, with a soil pH of 5.1 to 5.6. Research Method: This study is a descriptive analysis. The unit of analysis is the clove cultivation area in Petuanan Negeri Salamahu, Tehoru District, Central Maluku Regency. A sample of 4 clove land plots/groves in the Petuanan area of Negeri Salamahu was selected using Purposive Random Sampling. Results: For the same soil type across the four study locations, it was found that altitude, slope gradient, and tree age significantly influenced clove production. Cloves were more productive at altitudes below 114 meters above sea level, with a slope gradient of less than 20%.